2015
DOI: 10.1027/1866-5888/a000121
|View full text |Cite
|
Sign up to set email alerts
|

Control in Flexible Working Arrangements

Abstract: Supported by media technologies, today’s employees can increasingly decide when and where to work. The present study examines positive and negative aspects of this temporal and spatial flexibility, and the perceptions of control in these situations based on propositions of self-determination theory. Using an exploratory approach we conducted semi-structured interviews with 45 working digital natives. Participants described positive and negative situations separately for temporal and spatial flexibility, and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 22 publications
0
30
0
1
Order By: Relevance
“…Apparently, the range of choices of different activity settings falls short of fulfilling the need for autonomy of those workers who strongly feel this need. Referring to a study by Gerdenitsch et al [ 53 ], this may indicate that the freedom of choice in ABW environments is perceived as not only autonomously but also externally controlled. In this context, perceived external control might be related to social barriers (e.g., social norms) and practical barriers (e.g., limited availability of preferred settings) to using different activity settings freely.…”
Section: Discussionmentioning
confidence: 94%
“…Apparently, the range of choices of different activity settings falls short of fulfilling the need for autonomy of those workers who strongly feel this need. Referring to a study by Gerdenitsch et al [ 53 ], this may indicate that the freedom of choice in ABW environments is perceived as not only autonomously but also externally controlled. In this context, perceived external control might be related to social barriers (e.g., social norms) and practical barriers (e.g., limited availability of preferred settings) to using different activity settings freely.…”
Section: Discussionmentioning
confidence: 94%
“…CWs often involve the adoption of flexible work practices that provide people with the flexibility to collaborate across workgroups and functions, depending on the activity requirements (Bean and Eisenberg 2006;Ten Brummelhuis et al 2011;Hoeven and Zoonen 2015;Gerdenitsch et al 2015). This affects communication efficiency, information sharing and workplace support relationships (Collins et al 2016;Gajendran and Harrison 2007).…”
Section: Information and Communication Technologiesmentioning
confidence: 99%
“…Although this might be true in some cases, like flexible working arrangements (Gerdenitsch, Kubicek, & Korunka, 2015), there is also some evidence suggesting that a few changes are clearly negative. For example, it has been shown that workers appraise work intensification as a hindrance (Paškvan et al, 2016).…”
Section: Resultsmentioning
confidence: 98%